Pancreatic cancer-targeting exosomes for enhancing immunotherapy and reprogramming tumor microenvironment - Zhou, Wenxi; Zhou, Yu; Chen, Xinli; Ning, Tingting; Chen, Hongyi; Guo, Qin; Zhang, Yiwen; Liu, Peixin; Zhang, Yujie; Li, Chao; Chu, Yongchao; Sun, Tao; et al. (Biomaterials, 2021)
Immunotherapy has gained increasing focus in treating pancreatic ductal adenocarcinoma (PDAC), since conventional therapies like chemotherapy could not provide satisfactory improvement in overall survival outcome of PDAC patients. However, it is still not the game changing solution due to the unique tumor microenvironment and low cancer immunogenicity of PDAC. Thus, inducing more intratumoral effector immune cells as well as reversing immunosuppression is the core of PDAC treatment. Herein, we demonstrate an exosome-based dual delivery biosystem for enhancing PDAC immunotherapy as well as reversing tumor immunosuppression of M2-like tumor associated macrophages (M2-TAMs) upon disruption of galectin-9/dectin 1 axis. The deliver system is constructed from bone marrow mesenchymal stem cell (BM-MSC) exosomes, electroporation-loaded galectin-9 siRNA, and surficially modified with oxaliplatin (OXA) prodrug as an immunogenic cell death (ICD)-trigger. The use of biomaterials, BM-MSC exosomes, can significantly improve tumor targeting efficacy, thus increasing drug accumulation in the tumor site. The combined therapy (iEXO-OXA) elicits anti-tumor immunity through tumor-suppressive macrophage polarization, cytotoxic T lymphocytes recruitment and Tregs downregulation, and achieves significant therapeutic efficacy in cancer treatment. [Display omitted]